2002
DOI: 10.1097/00005537-200203000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neck Dissection for the Treatment of Neck Metastasis From Squamous Cell Carcinoma of the Head and Neck

Abstract: With similar indications for radiation therapy, the regional control rate in this cohort is comparable to control rates obtained with modified radical neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 15 publications
2
49
0
2
Order By: Relevance
“…Their reported pN0 rate was 57.4 % in this subset of patients, which is similar to our rate [12]. Chepeha et al reported comparable regional control rates in N+ patients undergoing SND followed by RT as compared to patients subjected to MND with RT [13]. Medina et al reported a 12.5 % regional failure rate in N+ patients undergoing SND and RT [14].…”
Section: Discussionsupporting
confidence: 86%
“…Their reported pN0 rate was 57.4 % in this subset of patients, which is similar to our rate [12]. Chepeha et al reported comparable regional control rates in N+ patients undergoing SND followed by RT as compared to patients subjected to MND with RT [13]. Medina et al reported a 12.5 % regional failure rate in N+ patients undergoing SND and RT [14].…”
Section: Discussionsupporting
confidence: 86%
“…Regional control in patients undergoing selective neck dissection with radiotherapy compared to modified neck dissections with radiotherapy has been demonstrated to be comparable in patients with a N0 to N2c nodal stage. 13 Regional recurrence rates are also comparable for radical (17.5%, CI 13.1-21.9) and modified radical neck dissections (14.3%; CI 7.1-21.5) with radiotherapy in patients with advanced neck disease (N2 or greater). 14 The regional recurrence rates reported in this study are, therefore, similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 78%
“…Of 4.5% neck recurrences after selective neck dissection, Carvalho et al (2000) found 57.1% of them to be inside the limits of dissection. Similarly, Anderson et al (2002) and Chepeha et al (2002) reported two-thirds of recurrences following SOHND to be in the field of dissection. Whitehurst and Droulias (1977) reported that 85% of the locoregional recurrences after surgical excision of tongue carcinoma occurred within 1 year, 95% within 2 years and 100% in 3 years.…”
Section: Discussionmentioning
confidence: 84%